Collaborating with Marine Birds to Monitor the Physical Environment Within Coastal Marine Protected Areas - Rachael Orben; Adam Peck-Richardson; Alexa Piggott; James Lerczak; Greg Wilson; Jessica Garwood; Xiaohui Liu; Sabir Muzaffar; Alexa Foster; Humood Naser; Mohamed AlMusallami; Tycho Anker-Nilssen; et al. (Oceanography, 2025)
Animal telemetry is maturing into a viable method for observing the ocean as it can be used to monitor both environmental conditions and biological metrics along the movement trajectories of marine animals. As part of the Cormorant Oceanography Project, we have augmented a biologging tag with an external fast response temperature sensor to collect ocean temperature profiles from the backs of foraging marine birds. Cormorants dive between 50 and 250+ times a day to forage for prey so they can provide hard-to-match temporal and spatial coverage of coastal ocean conditions within their foraging areas. We process tag measurements to obtain fundamental oceanographic data (e.g., temperature profiles, bottom soundings, surface current measurements). Together, we have tracked 17 marine bird species (including two Spheniscus penguins spp. and a sea duck), originating from 17 countries and foraging along the edges of all major oceans. Tagged birds’ distribution included 191 MPAs in 26 countries, offering a unique ocean monitoring method to complement more widely used methods.

Bioaccumulation of trace metal ions in the blue swimmer crab tissues Portunus pelagicus (Linnaeus, 1758) in Bahrain, Arabian Gulf - Ahmed S. Khamis; Humood A. Naser; Ahmed Y. Ali-Mohamed (Environmental Monitoring and Assessment, 2023)

Community Structures of Benthic Macrofauna in Reclaimed and Natural Intertidal Areas in Bahrain, Arabian Gulf - Humood Abdulla Naser (Journal of Marine Science and Engineering, 2022)
Costal reclamation has been carried out extensively along the coastlines of the Arabian Gulf during the last decades. As a small archipelago country, coastal reclamation continues to be a major option for securing land to meet the needs of the expanding population and economic development in Bahrain. Macrobenthic communities often reflect the integrity of ecosystems as they respond to natural and anthropogenic stressors. This study characterized the community structures of macrobenthic invertebrates in three reclaimed intertidal areas and a protected natural mudflat in Bahrain (August 2019 and December 2020). Macrobenthic community structures and sediment characteristics differed significantly between natural and reclaimed areas. A total of 43 species were recorded in the four study areas, of which 38 were collected from the natural mudflat. Polychaetes dominated macrobenthic communities, followed by molluscs and crustaceans. Polychaetes accounted for more than 90% of the communities in the reclaimed coastal areas. Macrobenthic monitoring is considered essential for detecting changes in coastal and marine ecosystems due to dredging and reclamation activities along the coastlines of the Arabian Gulf. The findings of this study can provide insights into the ecological dynamics of macrobenthic communities in reclaimed coastal areas for environmental monitoring and coastal planning and management in the Arabian Gulf.

Quantifying exposure levels of coastal facilities to oil spills in Bahrain, Arabian Gulf - Hassan Marzooq; Humood A. Naser; E. M. Elkanzi (Environmental Monitoring and Assessment, 2019)

Testing taxonomic resolution levels for detecting environmental impacts using macrobenthic assemblages in tropical waters - Humood A. Naser (Environmental Monitoring and Assessment, 2010)